Pemberdayaan Masyarakat dalam Penurunan Kemiskinan Ekstrem melalui Inovasi Pembuatan Sabun Cuci Piring: Studi KKN UINSU 2025 di Nagori Bandar Manik - Muhammad Rizky Hidayat; Erwan Efendi; Fadlan Arrasyid Bintang; Rahma Adlya Zahra; Luthfia Rizka Fadhila; Nurhasanah Hutabarat (Pusat Riset dan Inovasi Nasional, 2025)
Extreme poverty remains a major challenge in rural areas of Indonesia, including Nagori Bandar Manik, Pamatang Sidamanik District, Simalungun Regency. The 2025 UINSU Community Service Program (KKN) was carried out to empower local communities through various activities covering economic, educational, religious, social-environmental, and health aspects. This program employed a qualitative approach by involving active community participation in needs assessment, socialization, training, and evaluation. In the economic aspect, workshops on dishwashing liquid and herbal pesticide production were implemented as alternative household businesses. The educational sector included religious moderation through a short movie screening Mabbere, anti-bullying campaigns, ecoprint totebag training, and teaching at kindergarten, elementary, and junior high school levels. In the religious field, activities included Qur’an learning after Maghrib with children and Yasin recitals for both men and women. The social-environmental aspect was realized through community clean-up, educational boards on waste decomposition, distribution of garbage bins, and environmental awareness campaigns. Meanwhile, the health aspect focused on education about clean and healthy living behaviors, stunting prevention campaigns, and community exercise. The findings revealed improvements in entrepreneurial skills, children’s literacy, spiritual values, environmental awareness, and healthy lifestyles. The implication highlights that multidimensional community empowerment can serve as an effective strategy to reduce extreme poverty and promote sustainable village development.